2007
DOI: 10.1590/s0100-41582007000400012
|View full text |Cite
|
Sign up to set email alerts
|

Fungos associados a sementes de cevadilha vacariana (Bromus auleticus) coletadas nas plantas e no solo

Abstract: A espécie Bromus auleticus é uma gramínea perene nativa, com potencial para produção de forragem no outono-inverno, período de maior carência alimentar dos rebanhos bovino e ovino do sul do Brasil. O objetivo deste trabalho foi verificar a presença de microorganismos associados a sementes de B. auleticus, em função do momento de coleta, na planta e no solo. Os trabalhos de campo foram conduzidos na Embrapa Pecuária Sul, Bagé, estado do Rio Grande do Sul, em área semeada no ano de 1995. Em novembro de 2002 fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Any effective control alternative must investigate which fungi attack the seeds in specific regions (Silva et al, 2007;Senhor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Any effective control alternative must investigate which fungi attack the seeds in specific regions (Silva et al, 2007;Senhor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, seeds with greater TSM within the cultivars and places where the seeds studied were produced tend to be related to a higher percentage of AA, higher seedling length, and RL. Silva et al (2007), observed no influence on germination in seeds of rescue grass, but a positive influence on seed vigor, evaluated through AA and seedling length tests. In some cases, seeds of larger size or higher density have a larger amount of reserve for the embryo, tending to be more vigorous.…”
Section: Resultsmentioning
confidence: 88%
“…pode ter sido favorecido pela alta incidência de Rhizoctonia sp e Fusarium sp, uma vez que, nas análises realizadas foi verificada uma frequente associação entre estes fungos. Silva et al (2007) incidência de fungos como, Lasiodiplodia sp., Rhizoctonia sp., Fusarium sp. e Penicillium sp., os quais possuem algum risco potencial a integridade destas sementes, por serem organismos danosos a cultura da Palma-de-Óleo.…”
Section: Resultsunclassified